3-Trifluoromethylbenzyne: Precise Orientation in Cycloaddition Reaction Enabled Regioselective Synthesis of Trifluoromethylated Triptycenes - Iwata, Takayuki; Hyodo, Mizuki; Fujiwara, Takumi; Kawano, Ryusei; Kuhn, Leah; Alabugin, Igor V.; Shindo, Mitsuru (Synthesis, 2022)
The first regioselective addition reactions to 3-trifluoromethylbenzyne are reported. Triple cycloaddition of ynolates to the benzyne provided 1,8,13-tris(trifluoromethyl)triptycenes with high regioselectivity. 1-Trifluoromethyltriptycenes were regioselectively obtained by the Diels–Alder reaction of anthranoxides with the benzyne. These selectivities are attributed to the electron-acceptor nature of the trifluoromethyl group on the benzyne.
Keywords: benzynes; trifluoromethyl group; triptycenes; regioselective synthesis; cycloaddition; negative hyperconjugation